2022
DOI: 10.1136/neurintsurg-2021-018189
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of large and giant posterior communicating artery aneurysms with the Surpass streamline flow diverter: results from the SCENT trial

Abstract: BackgroundThe Surpass flow diverter was developed to treat intracranial aneurysms not amenable to standard treatment. Indications for use allow placement in the internal carotid artery to the terminus, including the communicating artery segment.MethodsThe Surpass Intracranial Aneurysm Embolization System Pivotal Trial to Treat Large or Giant Wide Neck Aneurysms (SCENT) trial is an international, multicenter, prospective, non-randomized trial comparing the outcomes of Surpass flow diverter treatment with histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Two patients died from the complications, one case presented a hemorrhage during retreatment of the target aneurysm, and the other had a fatal vessel perforation. 3,19 Details of the complications are provided in Supplemental Table 8 , http://links.lww.com/NEU/D806. Finally, the rate of PComA patency at final follow-up was 76% (CI 57%-89%, I 2 = 81%) (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two patients died from the complications, one case presented a hemorrhage during retreatment of the target aneurysm, and the other had a fatal vessel perforation. 3,19 Details of the complications are provided in Supplemental Table 8 , http://links.lww.com/NEU/D806. Finally, the rate of PComA patency at final follow-up was 76% (CI 57%-89%, I 2 = 81%) (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…21 That is of interest considering that jailing of the PComA carries a theoretical concern for vessel size reduction or occlusion which can lead to infarction in critical territories supplied by the lateral thalamic perforators such as the anterolateral thalamic nuclei, internal capsule, and optic tract. 3 Several studies have evaluated PComA patency after flow diversion, reporting occlusion rates ranging from 22% to 77%. We specifically found that the PComA patency rate was 76%.…”
Section: Safetymentioning
confidence: 99%
See 3 more Smart Citations